CAR-T Immunotherapy in oncological treatment: literature review (Research, Society and Development, 2022)
Introduction: Immunotherapies are developed to overcome limitations of conventional cancer therapy through stimulating innate immune response against tumor antigen. Objective: Elaborate a review on CAR-T Immunotherapy (Chimeric T Cell Antigen Receptor) in cancer treatment. Methods: Bibliographic survey of systematic reviews published in PubMed in the last 5 years. Results: 21 studies were selected. Antitumor effect occurs through cell lysis, due to CAR-T lymphocytes release of cytokines. Tumor escape is related to tumor's ability to not expose its Major Histocompatibility Complex (MHC) and/or inability of the adaptive immune system to recognize tumor antigens. These molecular targets may be proteins, carbohydrates, or glycolipids, with CD19 standing out as target of this therapy and in neoplasms as leukemia and lymphoma. Four generations of CARs have been described, which differ in terms of co-stimulatory domains and consequent functional efficiency. The therapy is indicated for cases of recurrence/refractoriness of hematological neoplasms, however applicability in solid tumors has been studied. Adverse events of CAR-T immunotherapy described were: cytokine release syndrome, neurotoxicity, anaphylactic shock, autoimmune reactions, B cell aplasia, tumor lysis syndrome and graft-versus-host disease. Conclusions: CAR-T immunotherapy is a promising therapy against relapsed/refractory cancer. It’s mainly used in leukemias and lymphomas. Choice of dose and generation of CARs should be cautious, considering specific molecular targets of each neoplasm and its presence in healthy tissues, avoiding adverse events.